A study on quality control during construction / Mohd Syahrizam Mahamad - Mahamad, Mohd Syahrizam (2002)
Several troublesome challenges face the local construction industry; productivity is down, litigation is up, delays are common and expensive. The reasons are complex, but one important common factor is quality or rather, the lack of it. The evolution of quality control is traced from nineteenth century to today explain the decline in quality studies and illustrate the need for new approach. The study consists of a research about Quality Control in Construction. The main objective of the research is to determine awareness on the quality control system approaches among contractors. It is also to identify the critical problems that affected the quality control in construction, furthermore, the study also to determine the benefits of quality control implementation in construction project. The research findings indicate that the quality control in construction must be increased in every project from beginning to completion. The critical problems that affect the quality control of construction are the commitment from top management towards quality achievement, coordination and communication among members in teamwork, completion of project within schedule and completion of project within budget. Recommendations to overcome this problem have been included in this research. I hope that this report will useful not merely to contractors but also to others may be involved in construction project.